Effect of information communication technology infrastructure on performance of county government of Migori, Kenya - Otwal, Walter; Midida, Peterson; Aliata, Victor L. (My University, 2021)
An adoption of electronic procurement aspects is currently indispensable in many organizations. However county government of Migori has not embraced this technological change as expected and hence affecting its performance. Most reviewed studies failed to link the aspects of electronic procurement adoption to the organizational performance. They were mostly exploratory in design and did not focus on the county government of Migori in particular. Small samples and convenient sampling techniques dominated these studies. The purpose of this study, therefore, was to establish the effect of information communication technology infrastructure on performance of county government of Migori, Kenya. This study was anchored on the following theories; diffusion of innovation (DOI), technology acceptance model theory (TAM), universality theory, contingency theory and organizational performance theory which formed part of this study. The study adopted a correlation research design. Census sampling was embraced. The target population was 50 comprising of procurement officers, procurement staff, top management and directors working in the county government of Migori. Questionnaires were used in collecting primary data while secondary data was obtained from existing literature. The findings revealed that ICT infrastructure had the strongest unique contribution on organizational performance (β=.463, p=.000). The study concluded that ICT infrastructure is a significant predictor of organizational performance and therefore have a positive effect. The study recommends that the county government of Migori provides more infrastructures for electronic procurement adoption. The study will be of significance to stakeholders in the enhancement of performance through electronic procurement and addressing the gaps especially in the county government of Migori. To the academia, it will add value to new knowledge for further research. To policy makers, the study will assist in the identification of issues raised in different areas to improve organizational performance more so in the county government of Migori.
DOI: 10.47191/ijmei/v7i3.01
Keywords: Electronic Procurement; Information Communication Technology Infrastructure; Performance; County Government of Migori; Kenya